Endovascular Treatment of Atherosclerotic Tandem Occlusions in Anterior Circulation Stroke: Technical Aspects and Complications Compared to Isolated Intracranial Occlusions - Eker, Omer Faruk; Bühlmann, Monika; Dargazanli, Cyril; Kaesmacher, Johannes; Mourand, Isabelle; Gralla, Jan; Arquizan, Caroline; Fischer, Urs Martin; Gascou, Gregory; Heldner, Mirjam; Arnold, Marcel; Costalat, Vincent; et al. (Frontiers in Neurology, 2018)
Background and Purpose: Endovascular treatment of tandem occlusions is an emerging option. We describe our multicenter experience with endovascular management of atherosclerotic tandem occlusions in the anterior circulation, particularly the technical aspects and complications in comparison to isolated intracranial occlusions. Materials and Methods: Consecutive patients with tandem occlusions due to atherosclerotic causes who underwent mechanical thrombectomy at two major stroke centers between January 2010 and September 2015 were reviewed. Clinical data, procedural aspects, recanalization rates, complication rates, and clinical outcome were analyzed and compared to findings in patients with isolated intracranial occlusions. Results: One hundred and twenty-one patients with tandem occlusions and 456 patients with isolated intracranial occlusions (carotid-T/M1) were included. Mean intervention time was faster (33 min vs 57 min, p<0.001) and recanalization success was higher (TICI 2b/3 83.6% vs 70.2%, p=0.002) in patients with isolated occlusions. No difference was seen in clinical outcome and complications, except for a higher rate of asymptomatic hemorrhage in the tandem group (29.8% vs 17.1%, p=0.003). Choice of recanalization approach (antegrade vs retrograde) in the tandem group made no difference, except for a trend toward less distal emboli using the retrograde approach (4.0% vs 13.0%, p=0.082). Stenting of the extracranial internal carotid artery (ICA) was performed in 81%, PTA alone in 7.4%, and deferred stenting in 11.6%. Rate of stent/ICA occlusion within 7 days was 10.3% after stenting and 33.3% after PTA (p=0.127). In the tandem group, age (p=0.034), National Institutes of Health Stroke Scale score (NIHSS) at admission (p=0.002), recanalization rate (p<0.001), complications (p=0.016), and symptomatic intracranial hemorrhage (sICH) (p=0.001) were associated with poor outcome, whereas extracranial treatment modality and stent/ICA occlusion within 7 days did not affect outcome. Conclusion: Endovascular treatment of tandem occlusions is technically feasible, achieves recanalization rates and rates of good clinical outcome comparable to those in patients with isolated intracranial occlusions. Following acute ICA stenting, the risk of stent occlusion and sICH appeared to be low, but was associated with an increased rate of asymptomatic ICH.